Evaporative characteristics of winter wheat in the guanzhong loess plateau region of shaanxi, china (Bangladesh Journal of Botany, 2024)
This study explain the evaporative characteristics of winter wheat in the Guanzhong Loess Plateau region of Shaanxi through stem flow meters and weighing lysimeters. It examines the diurnal variations in evapotranspiration rates, leaf area index, and soil moisture's impact on winter wheat evaporation. Additionally, it explores the ratio of transpiration to evaporation and compares the evaporation measured by the water balance method with that of the lysimeters. The findings reveal distinct diurnal variations in transpiration rates under different weather conditions, with sunny days exhibiting an unimodal curve while cloudy and rainy days showcase irregular multi-peaked curves. The evaporation curve generally follows an unimodal pattern, with both leaf area index and soil moisture significantly influencing the evaporation process. From heading to early grain filling, the ratio of transpiration to evaporation ranges from 80.3  to 83.4%. Evaporation obtained through the water balance method (0-220 cm) is 6% less than that measured by the lysimeters.Bangladesh J. Bot. 53(3): 689-695, 2024 (September) Special